Time‐ and Space‐Resolved Flow‐Cytometry of Cell Organelles to Quantify Nanoparticle Uptake and Intracellular Trafficking by Cells. Issue 34 (17th July 2021) - Garcia Romeu, Hector; Deville, Sarah; Salvati, Anna
Abstract: The design of targeted nanomedicines requires intracellular space‐ and time‐resolved data of nanoparticle distribution following uptake. Current methods to study intracellular trafficking, such as dynamic colocalization by fluorescence microscopy in live cells, are usually low throughput and require extensive analysis of large datasets to quantify colocalization in several individual cells. Here a method based on flow cytometry to easily detect and characterize the organelles in which nanoparticles are internalized and trafficked over time is proposed. Conventional cell fractionation methods are combined with immunostaining and high‐sensitivity organelle flow cytometry to get space‐resolved data of nanoparticle intracellular distribution. By extracting the organelles at different times, time‐resolved data of nanoparticle intracellular trafficking are obtained. The method is validated by determining how nanoparticle size affects the kinetics of arrival to the lysosomes. The results demonstrate that this method allows high‐throughput analysis of nanoparticle uptake and intracellular trafficking by cells, therefore it can be used to determine how nanoparticle design affects their intracellular behavior. Abstract : Flow cytometry of organelles allows to determine nanoparticle distribution and intracellular trafficking kinetics with easy and robust quantification. This is a complementary tool to the existing methods to characterize and quantify intracellular trafficking of nanoparticles, which are mainly based on imaging.